The VIKOR algorithm in material decision support - Takács, Ágnes; Albert, Judit (Design of Machines and Structures, 2024)
The paper presents how to deal with frequent decision conflicts between design criteria that arise when selecting complex materials. The results show that the VIKOR model, in this case study, can also be used for extensive exploration of trade-offs and design return points, such as changes in environmental, material performance, and cost characteristics for the decision maker during design. In this paper, we examine the problem-solving algorithm for implementation.